2022
DOI: 10.1007/s10388-022-00972-z
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of taxanes following nivolumab in patients with advanced esophageal squamous cell carcinoma: a retrospective chart review of patients in ATTRACTION-3

Abstract: Background The phase III ATTRACTION-3 study showed that second-line nivolumab monotherapy for advanced esophageal squamous cell carcinoma prolonged overall survival (OS) but did not improve progression-free survival (PFS). Subsequent systemic therapy after discontinuing nivolumab may affect these outcomes. To test this possibility, we evaluated the outcomes of treatment with taxanes after nivolumab in ATTRACTION-3. Methods We reviewed the charts of Japanes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…A previous retrospective chart review of Japanese patients (ATTRACTION-3 trial) demonstrated the effectiveness of taxanes following nivolumab treatment. The ORR, median PFS, and median OS were 29.6%, 4.9 months, and 9.9 months, respectively [23]. When the ORR, PFS, and OS reported in the current study were compared with those of previous studies, the results showed that the ORR was more favorable, while the PFS and OS were comparable [3,4,24].…”
Section: Discussionsupporting
confidence: 48%
“…A previous retrospective chart review of Japanese patients (ATTRACTION-3 trial) demonstrated the effectiveness of taxanes following nivolumab treatment. The ORR, median PFS, and median OS were 29.6%, 4.9 months, and 9.9 months, respectively [23]. When the ORR, PFS, and OS reported in the current study were compared with those of previous studies, the results showed that the ORR was more favorable, while the PFS and OS were comparable [3,4,24].…”
Section: Discussionsupporting
confidence: 48%
“…Vincristine and vinblastine were the first samples of this grain had divergent degrees of anti-tumor activity. Cancers treated with these consolidations include Hodgkin's/non-Hodgkin's lymphomas, leukaemias, rhabdomyosarcoma, Ewing's sarcoma, neuroblastoma, miscellaneous myeloma, thyroid neoplasms, brain lesions, and several blood related disorders (43,44) . The Table provided a description details of the anti-neoplastic agents.…”
Section: Mitotic Spindle Inhibitorsmentioning
confidence: 99%